Optimization of sowing date and seeding rate for high winter wheat yield based on pre-winter plant development and soil water usage in the Loess Plateau, China - Ai-xia REN; Min SUN; Pei-ru WANG; Ling-zhu XUE; Miao-miao LEI; Jian-fu XUE; Zhi-qiang GAO; Zhen-ping YANG (Journal of Integrative Agriculture, 2019)
Sowing date and seeding rate are critical for productivity of winter wheat (Triticum aestivum L.). A three-year field experiment was conducted with three sowing dates (20 September (SD1), 1 October (SD2), and 10 October (SD3)) and three seeding rates (SR67.5, SR90, and SR112.5) to determine suitable sowing date and seeding rate for high wheat yield. A large seasonal variation in accumulated temperature from sowing to winter dormancy was observed among three growing seasons. Suitable sowing dates for strong seedlings before winter varied with the seasons, that was SD2 in 2012–2013, SD3 in 2013–2014, and SD2 as well as SD1 in 2014–2015. Seasonal variation in precipitation during summer fallow also had substantial effects on soil water storage, and consequently influenced grain yield through soil water consumption from winter dormancy to maturity stages. Lower consumption of soil water from winter dormancy to booting stages could make more water available for productive growth from anthesis to maturity stages, leading to higher grain yield. SD2 combined with SR90 had the lowest soil water consumption from winter dormancy to booting stages in 2012–2013 and 2014–2015; while in 2013–2014, it was close to that with SR67.5 or SR112.5. For productive growth from anthesis to maturity stages, SD2 with SR90 had the highest soil water consumption in all three seasons. The highest water consumption in the productive growth period resulted in the best grain yield in both low and high rainfall years. Ear number largely contributed to the seasonal variation in grain yield, while grain number per ear and 1 000-grain weight also contributed to grain yield, especially when soil water storage was high. Our results indicate that sowing date and seeding rate affect grain yield through seedling development before winter and also affect soil water consumption in different growth periods. By selecting the suitable sowing date (1 October) in combination with the proper seeding rate of 90 kg ha–1, the best yield was achieved. Based on these results, we recommend that the current sowing date be delayed from 22 or 23 September to 1 October.